Pengaruh Literasi Keuangan Terhadap Pengeloaan Keuangan Umkm Kedai Utuy Pulojaya Lemahabang - Hoeriah Hoeriah; Dini Yani; Puji Isyanto (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The level of education affects financial management as seen from indicators of understanding work and also business actors understand the prospects for the business to be carried out in the future, so that financial understanding is needed. Lack of financial literacy or understanding of MSME actors about finance makes MSME actors wrong in financial management or financial planning still low. In making financial decisions effectively and efficiently a business actor is required to have good knowledge of financial management, this ability is known as financial literacy. This study aims to determine the effect, level of education, income, understanding of financial literacy and financial attitudes on the behavior of financial managers in Micro, Small and Medium Enterprises (MSMEs) actors have several different definitions in each literature according to agencies or institutions and even laws. After conducting an interview with one of the MSMEs, it can be compared with the theoretical basis obtained from some of the literature that supports this writing. So the existence of financial literacy for MSMEs can help in managing MSME finances in terms of their profits and expenses.